PEDAGOGICAL APPROACHES TO DEVELOPING STUDENTS’ DRAWING SKILLS IN VISUAL ARTS LESSONS - Ataullayeva E’zoza Mansur qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines pedagogical strategies for developing students’ drawing skills in visual arts lessons. Drawing on the research of Shovdirov S.A., it highlights interactive teaching methods, practical exercises, and creative assignments as effective tools for enhancing students’ technical abilities, artistic thinking, and independent work. The study also discusses the role of guided practice, group collaboration, and constructive feedback in fostering students’ aesthetic perception and problem-solving skills.